2016
DOI: 10.3390/nu8070419
|View full text |Cite
|
Sign up to set email alerts
|

Food Habits, Lifestyle Factors, and Risk of Prostate Cancer in Central Argentina: A Case Control Study Involving Self-Motivated Health Behavior Modifications after Diagnosis

Abstract: Cancer is the second most important non-communicable disease worldwide and disproportionately impacts low- to middle-income countries. Diet in combination with other lifestyle habits seems to modify the risk for some cancers but little is known about South Americans. Food habits of Argentinean men pre- and post-diagnosis of prostate cancer (n = 326) were assessed along with other lifestyle factors. We studied whether any of the behaviors and risk factors for prostate cancer were found in men with other cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 121 publications
(127 reference statements)
2
12
0
5
Order By: Relevance
“…The fact that the elderly show, at the present, a better lifestyle than other participants of our study, in regard to smoking, alcohol consumption and intake of fruit and vegetables, may be associated with a previous history of a medical diagnosis of chronic diseases. Indeed, a recent study from our group showed that positive lifestyle changes, especially dietary modifications, occur after the diagnosis of prostate cancer and in other types of cancer in men [57]. Similar observations have also been reported by other investigators [58,59,60].…”
Section: Discussionsupporting
confidence: 85%
“…The fact that the elderly show, at the present, a better lifestyle than other participants of our study, in regard to smoking, alcohol consumption and intake of fruit and vegetables, may be associated with a previous history of a medical diagnosis of chronic diseases. Indeed, a recent study from our group showed that positive lifestyle changes, especially dietary modifications, occur after the diagnosis of prostate cancer and in other types of cancer in men [57]. Similar observations have also been reported by other investigators [58,59,60].…”
Section: Discussionsupporting
confidence: 85%
“…Participants were asked about their education (primary or illiterate, intermediate, high school, academic), occupation (housewife, employed), ethnicity (Fars, Lor, Turk, other), family history of breast cancer (no, second relative, first relative/both first and second relatives), smoking during adolescence and adulthood (yes, no), history of oral contraceptive (OCP) use (ever, never), history of chest X‐ray (yes, no), history of benign breast disease (yes, no), physical activity (30 min or more of moderate aerobic exercise at least three times per week on a regular basis) (yes, no), body mass index (BMI; defined as <24.9, 25.0 to 29.9 and ≥30.0 kg/m 2 ), deliberate weight loss after 18 years of age (yes, no), age at first delivery (<18, 18–23, 24–30, ≥31 years and nulliparous), total number of months of breastfeeding for all children (0–5, 6–17, 18–29, 30–41, ≥42 months), history of miscarriage (yes, no), menarche age (<12, 12–13, ≥14 years), regular menstrual (yes, no), menopausal status (premenopausal, postmenopausal), and diagnosed with type 2 diabetes (yes, no).…”
Section: Methodsmentioning
confidence: 99%
“…Considering results of cohort studies published between 2007 and 2017, eight studies did not identify a significant impact of smoking status or habits on PCa risk [10][11][12][13][14][15][16][17], while another 10 studies showed an inverse association of smoking with reduced PCa risk [18][19][20][21][22][23][24][25][26][27]. On the contrary, when reviewing case-control studies (CCSs), only two studies did not find an impact on PCa incidence [28,29]: a study from Argentina found the same proportion of smokers in patients with PCa and controls [28]; also, May et al [20] did not find significant differences in the rate of advanced tumor stages between smokers and nonsmokers, while overall PCa risk was not evaluated. However, most CCSs found either an increased risk for PCa or more frequent high-grade PCa (HGPCA) and advanced stages in smokers [31][32][33][34][35][36][37].…”
Section: Smoking and Risk For Pcamentioning
confidence: 99%